2010
DOI: 10.1007/s10571-010-9541-9
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Binds to GluR2 mRNA and CaM1 mRNA in the Brain and Regulates their Translational Levels in an Activity-Dependent Manner

Abstract: The translational regulator YB-1 binds to mRNAs. In the brain, YB-1 is prominently expressed from the prenatal stage until the first week after birth, being associated with polysomes and distributed in neuronal dendrites, but its expression declines to a much lower level thereafter. It is therefore of interest to identify the mRNAs whose translation is controlled by YB-1 in the postnatal growing brain. In this study we found that YB-1 interacted with the mRNAs for glutamate receptor subunit 2 (GluR2) and calmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…We subsequently analysed YB-1 bound and input RNA using whole genome microarrays and found among others YB-1 mRNA itself, α - tubulin , EEF2 and UBC mRNA enriched in the PCT IP sample, which is in agreement with published data from both in-vitro systems and cell lines. 2931 Importantly, MYC mRNA was found within the top 100 entries. Moreover, we observed a significant enrichment of several mRNAs associated with MYC pathways among the top 500 IP-specific entries (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently analysed YB-1 bound and input RNA using whole genome microarrays and found among others YB-1 mRNA itself, α - tubulin , EEF2 and UBC mRNA enriched in the PCT IP sample, which is in agreement with published data from both in-vitro systems and cell lines. 2931 Importantly, MYC mRNA was found within the top 100 entries. Moreover, we observed a significant enrichment of several mRNAs associated with MYC pathways among the top 500 IP-specific entries (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of known targets of YB-1 assisted translation ( α - tubulin , EEF2 , UBC ) validated our approach, but the majority of mRNAs presented here have not been identified as YB-1 targets before and hence are novel. 29,31 GSEA analysis of IP transcripts in each sample showed a significant enrichment for either directly MYC-driven pathways or those that had an indirect relationship to MYC (Supplementary Table 2). Taken together, the data on co-expression and direct binding of YB-1 to wild-type MYC mRNA imply that YB-1 is involved in MYC overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Y-boxbinding protein 1 (YB-1) is a multifunctional protein that binds DNA and RNA and plays an important role in transcriptional and translational regulation (30,31). A recent study indicated that YB-1 interacts with Eaat2 mRNAs in the mouse brain (32). To examine whether YB-1 is involved in compound-activated EAAT2 translation, we performed siRNA knockdown experiments and found that depletion of YB-1 markedly reduced LDN/OSU-0212320-induced EAAT2 expression in PA-EAAT2 cells ( Figure 6A).…”
Section: Figurementioning
confidence: 99%
“…This raises the exciting possibility that this mechanism of translational control might regulate Nodal signaling in different developmental, physiological, and pathological contexts in humans, and warrants further exploration. Notably, human YBX1 has been found in mRNPs in neurons, a cell type known for extensive RNA transport, subcellular localization and localized translation ( 71 74 ). Furthermore, Ybx1 has been proposed as a facilitator of RNA transport/localization by recruiting RNAs to the cytoskeleton ( 16 ).…”
Section: Discussionmentioning
confidence: 99%